INTEGRATED MANAGEMENT SCHEDULE FOR CONTROL OF BLACK SCURF DISEASE OF POTATO CAUSED BY RHIZOCTONIA SOLANI - Singh, Rajpal; Paul Khurana, S. M.; Singh, B P.; Bhat, M. Narayana (Potato Journal, 2013)
The integrated approach which includes use of disease free seed, 3% boric acid as tuber spray, soil application of gypsum @ 15 q/ha along with fertilizer before planting, light irrigation at 15-20 days interval, soil pulverization, hot weather cultivation (HWC), harvesting within 20 days after dehaulming and potato based crop rotation-Potato-HWC: GM-Potato proved to be the best for managing the black scurf disease of potato. The above-integrated management reduced the disease incidence from 71.2% (control)to 4.8% and population buildup from 5x107 to 0x102 propagules/g soil.